Critical Ecospirituality for the Realization of the Bonum Commune and Agrarian Justice in Sekadau, West Kalimantan: A Postcolonial Deconstructive Approach - Kwirinus, Dismas; Wijanarko, Robertus; Tjatur Raharso, Alphonsus; Dendi, Ignatius (Jayapangus Press, 2025)
Environmental degradation in Sekadau, West Kalimantan, demonstrates that the ecological crisis is also a spiritual and moral crisis rooted in structural inequalities between Indigenous communities and capitalist powers. This study aims to examine the theological and ethical dimensions of critical eco-spirituality as a transformative paradigm for advancing the bonum commune and agrarian justice within a postcolonial context. Using a literature review and hermeneutical theological reflection through critical discourse analysis of theological texts, agrarian policies, and Indigenous narratives, this research identifies forms of spiritual resistance emerging from the ecological and social experiences of the Dayak community. The findings show that critical eco-spirituality integrates ecological awareness with transformative ethical praxis that is inherently political, grounded in the intersubjective relationship between humans, nature, and the Transcendent, and challenges the exploitative logic of colonial and neoliberal legacies. The study concludes that local spiritual values such as cosmic harmony and ecological solidarity can serve as an alternative epistemology for justice-oriented development. Critical eco-spirituality thus offers a new theological paradigm capable of strengthening inclusive and participatory socio-political agrarian praxis while affirming the cultural autonomy of Indigenous communities in the face of modern hegemonic pressures.